Esensi Pendidikan Akhlak dalam Novel Cinta Subuh Karya Alii Farighi - Fitri, Susi Susanti; Syafei, Syafei (An-Nuha, 2023)
In Islam, morality is something that is closely related to faith and cannot be separated. In an Islamic perspective, character or morals have a very high position (Bafadhol, 2017). This study aims, (1) to find out whether there are moral education values ​​for peers in Alii Farighi's novel Cinta Subuh. (2), to find out the essence of youth moral education towards peers in the novel Cinta Subuh by Alii Farighi. This research method is qualitative with a content analysis approach. This type of research is library research. The results of this study are first, there are values ​​of moral education towards peers in the novel Cinta Subuh by Alii Farighi. Second, the essence of moral education towards peers in the novel Cinta Subur includes; ; morals in speaking, tawadhu', advising each other, loving and helping each other, being honest and forgiving each other.